Mind the GAP: Purification and characterization of urea resistant GAPDH during extreme dehydration. Issue 5 (6th January 2021) - Hadj‐Moussa, Hanane; Wade, Steven C.; Childers, Christine L.; Storey, Kenneth B.
Abstract: The African clawed frog ( Xenopus laevis ) withstands prolonged periods of extreme whole‐body dehydration that lead to impaired blood flow, global hypoxia, and ischemic stress. During dehydration, these frogs shift from oxidative metabolism to a reliance on anaerobic glycolysis. In this study, we purified the central glycolytic enzyme glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) to electrophoretic homogeneity and investigated structural, kinetic, subcellular localization, and post‐translational modification properties between control and 30% dehydrated X. laevis liver. GAPDH from dehydrated liver displayed a 25.4% reduction in maximal velocity and a 55.7% increase in its affinity for GAP, as compared to enzyme from hydrated frogs. Under dehydration mimicking conditions (150 mM urea and 1% PEG), GAP affinity was reduced with a K m value 53.8% higher than controls. Frog dehydration also induced a significant increase in serine phosphorylation, methylation, acetylation, beta‐N‐acetylglucosamination, and cysteine nitrosylation, post‐translational modifications (PTMs). These modifications were bioinformatically predicted and experimentally validated to govern protein stability, enzymatic activity, and nuclear translocation, which increased during dehydration. These dehydration‐responsive protein modifications, however, did not appear to affect enzymatic thermostability as GAPDH melting temperatures remained unchanged when tested with differential scanning fluorimetry. PTMs could promote extreme urea resistance in dehydrated GAPDH since the enzyme from dehydrated animals had a urea I50 of 7.3 M, while the I50 from the hydrated enzyme was 5.3 M. The physiological consequences of these dehydration‐induced molecular modifications of GAPDH likely suppress GADPH glycolytic functions during the reduced circulation and global hypoxia experienced in dehydrated X. laevis .